2001
DOI: 10.1046/j.1471-4159.2001.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression differences in bipolar disorder revealed by cDNA array analysis of post‐mortem frontal cortex

Abstract: Previous studies have implicated a number of biochemical pathways in the etiology of bipolar disorder (BD). However, the precise abnormalities underlying this disorder remain to be established. To investigate novel factors that may be important in the pathophysiology of BD, we utilized cDNA expression arrays to examine differences in expression of up to 1200 genes known to be involved in potentially relevant biochemical processes. This investigation was undertaken in post-mortem samples of frontal cortex tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 67 publications
2
43
0
Order By: Relevance
“…Previous microarray studies using post-mortem brains from BD1 patients have found differential expression of genes related to apoptosis and neuroprotection; 35,36 neurotransmission and energy metabolism; 37 mitochondrial function; 37,38 receptor/transport, stress response, molecular chaperones and transcription factors; 33 signal transduction; 33,35 myelination and oligodendrocyte function 39 and ubiquitin cycle and synaptic-related genes. 40 Microarray studies assessing white blood cell-derived gene expression levels in BD1 have found, among many different processes, aberrations in RNA binding and ribosomal function, 6 as well as the ER stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous microarray studies using post-mortem brains from BD1 patients have found differential expression of genes related to apoptosis and neuroprotection; 35,36 neurotransmission and energy metabolism; 37 mitochondrial function; 37,38 receptor/transport, stress response, molecular chaperones and transcription factors; 33 signal transduction; 33,35 myelination and oligodendrocyte function 39 and ubiquitin cycle and synaptic-related genes. 40 Microarray studies assessing white blood cell-derived gene expression levels in BD1 have found, among many different processes, aberrations in RNA binding and ribosomal function, 6 as well as the ER stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray work has revealed decreases in metabolic-associated transcripts in bipolar disorder. 91,92 However, decreased metabolic-associated transcripts have been associated with decreased brain pH, 34 a common confounding factor in psychiatric postmortem brain research. Due to this latter finding, it is important to interpret with care the data that is obtained from the Stanley array data set, which is not corrected for brain pH, as the mean values in the schizophrenia and bipolar groups are lower than in the control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Some microarray studies have not reported a broad mitochondrial gene expression pattern in BPD (72,73) or SZ (62,74,75). A few microarray studies in MDD have not reported that mitochondrial genes were differentially expressed in cortex (76)(77)(78).…”
Section: Altered Mitochondrial Gene Expression In Psychiatric Disordersmentioning
confidence: 99%